Influence of incongruent dissolution-precipitation on 8YSZ ceramics during cold sintering process. Issue 5 (May 2022) - Huang, Yuming; Huang, Kaiming; Zhou, Shiyong; Lin, Cong; Wu, Xiao; Gao, Min; Zhao, Chunlin; Fang, Changqing
Abstract: The incongruent dissolution-precipitation behaviors of 8YSZ (8 mol% yttria-stabilized zirconia) ceramics during cold sintering process is studied in this paper by changing the pH of liquid media. The different solubility of Y 3+ and Zr 4+ at the same lattice position causes the disparate dissolution behaviors, and results in incongruent precipitation. Compared with acidic or alkaline solution, neutral solution is more conducive to the incongruent dissolution-precipitation process, and the concentration ratio of dissolved Y 3+ and Zr 4+ can reach ∼6385. The incongruent dissolution-precipitation process facilitates the formation of neck structure and promotes the ionic migration and diffusion at the subsequent high-temperature sintering process, which improves the mechanical properties and electrochemical properties of 8YSZ ceramics. This work reveals the principle of incongruent dissolution-precipitation process of zirconia-based ceramics, and it is of significance for selecting suitable liquid media to control the incongruent dissolution-precipitation behaviors in cold sintering process to prepare high-performance zirconia-based ceramics.